Comprehensive Tools for Culturing Blastocystis: A Standardized Resource for Research and Diagnostics - Shaw, Daisy; Denoyelle, Constance; Tan, Kevin S W; Clark, C Graham; Yoshikawa, Hisao; Viscogliosi, Eric; Gentekaki, Eleni; Jirků, Kateřina; Tsaousis, Anastasios D (Current protocols, 2025)
Blastocystis spp. is a widely prevalent anaerobic protozoan of uncertain pathogenicity found in the gastrointestinal tracts of over 1 billion people worldwide. Despite its potential significance in health and disease, Blastocystis spp. remains challenging to culture axenically due to its anaerobic nature and the diversity of its genetic subtypes. This manuscript presents a standardized toolkit for culturing Blastocystis spp. in xenic and axenic conditions, detailing protocols for the preparation of appropriate liquid and solid media, cryopreservation, and inoculation. By providing a comprehensive set of tools and methodologies, this work aims to streamline research on Blastocystis spp., enabling reproducibility, subtype characterization, and advancements in understanding its role in the gut microbiome and host health. © 2025 The Author(s). Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1: Establishment of xenic Blastocystis culture from stool samples in liquid medium Basic Protocol 2: Subculturing from existing Blastocystis liquid culture Support Protocol 1: Preparation of modified Jones' medium for Blastocystis culturing Support Protocol 2: Preparation of trypticase-yeast extract-serum-gastric mucin-9 (TSGYM-9) medium for Blastocystis culturing Support Protocol 3: Preparation of liver extract-yeast extract-serum-gastric mucin (LYSGM) medium for Blastocystis culturing Basic Protocol 3: Subculturing xenic Blastocystis cultures in diphasic medium Support Protocol 4: Preparation of Robinson's medium for Blastocystis culturing Support Protocol 5: Preparation of Ringer's agar slants for Blastocystis culturing Basic Protocol 4: Axenization of Blastocystis cultures Basic Protocol 5: Subculturing axenic Blastocystis cultures in diphasic medium Support Protocol 6: Preparation of Boeck and Drbohlav's Locke-egg serum (LES) medium for Blastocystis culturing Support Protocol 7: Preparation of Boeck and Drbohlav's diphasic modified medium (BDMM) for Blastocystis culturing Basic Protocol 6: Establishment of axenic Blastocystis cultures in Iscove's modified Dulbecco's medium (IMDM) Basic Protocol 7: Establishment of axenic Blastocystis cultures in soft IMDM agar Basic Protocol 8: Establishment of axenic Blastocystis cultures on solid IMDM agar Basic Protocol 9: Optimized method for establishing axenic Blastocystis cultures on solid IMDM agar Basic Protocol 10: Establishment of axenic Blastocystis cultures in semi-solid Locke's agar Basic Protocol 11: Cryopreservation of xenic Blastocystis cultures Basic Protocol 12: Cryopreservation of axenic Blastocystis cultures Basic Protocol 13: Inoculation of liquid medium with xenic Blastocystis cultures from frozen stocks Basic Protocol 14: Inoculation of liquid medium with axenic Blastocystis cultures from frozen stocks.
Keywords: blastocystóza; Feces; blastocystis; Blastocystis Infections; Culture Media; Blastocystis; culturing; kryoprezervace; lidé; in vitro; feces; Humans; kultivační média; Cryopreservation